Misuse of Statistical Methods in 10 Leading Chinese Medical Journals in 1998 and 2008 - Shunquan Wu; Zhichao Jin; Xin Wei; Qingbin Gao; Jian Lu; Xiuqiang Ma; Cheng Wu; Qian He; Meijing Wu; Rui Wang; Jinfang Xu; Jia He (The Scientific World Journal)
Statistical methods are vital to biomedical research. Our aim was to find out whether progress has been made in the last decade in the use of statistical methods in Chinese medical research. We reviewed 10 leading Chinese medical journals published in 1998 and in 2008. Regarding statistical methods, using a multiple t-test for multiple group comparison was the most common error in the t-test in both years, which significantly decreased in 2008. In contingency tables, no significant level adjustment for multiple comparison significantly decreased in 2008. In ANOVA, over a quarter of articles misused the method of multiple pair-wise comparison in both years, and no significant difference was seen between the two years. In the rank transformation nonparametric test, the error of using multiple pair-wise comparison for multiple group comparison became less common. Many mistakes were found in the randomised controlled trial (56.3% in 1998; 67.9% in 2008), non- randomised clinical trial (57.3%; 58.6%), basic science study (72.9%; 65.5%), case study or case series study (48.4%; 47.2%), and cross-sectional study (57.1%; 44.2%). Progress has been made in the use of statistical methods in Chinese medical journals, but much is yet to be done.